Peritoneal Dialysis in the elderly: challenge accepted - Lança, A. (2018)
At present, mostly in Western countries, age is no longer an absolute limitation for renal replacement therapy (RRT); however, some elderly patients are still not considered for peritoneal dialysis (PD), mainly due to late referral, social isolation, low functional capacity or lower life expectancy. In this review, we address the challenges posed by older patients on PD programs, focusing on a SWOT (strengths, weaknesses, opportunities and threats) analysis and illustrate how PD may have successful outcomes in this population, worldwide and in Portugal. Finally, we will enumerate strategies to overcome the barriers to this technique. From January to December 2017, we conducted a systematic review of the literature using MEDLINE, the Cochrane Library and Web of Knowledge. Studies on PD and HD were included. All searches were limited to English and Portuguese and were augmented by review of bibliographic references from the studies included. Findings concerning modality superiority and better outcome in older people are still scarce and controversial, however according to several well-established PD programs worldwide, including assisted PD, elderly patients presented similar technique survival, hospitalization rates and frequency of peritonitis as compared to younger PD patients and HD patients. As expected, older patients had higher mortality though, especially in patients with more comorbidities. On the other hand, PD was associated with less cognitive loss and showed benefit in perceived quality of life. In Portugal, the low utilization of PD and the patients’ age discrepancy between both modalities explains the limited literature and the discrepante results (some studies show lower peritonitis rate, superior technique and patient survival and others presente higher hospitalization episodes and mortality rates); however, it appears to be a good (cost-effective) option for elderly patients. Overall, PD is an equally suitable modality for elderly patients in the long term.